Leucocyte complement receptor 1 (CR1/CD35) transcript and its correlation with the clinical disease activity in rheumatoid arthritis patients. (June 2014) - Anand, D.; Kumar, U.; Kanjilal, M.; Kaur, S.; Das, N.
Summary In view of the exaggerated complement activation in rheumatoid arthritis (RA) and significance of complement receptor 1 (CR1/CD35) as a complement regulatory protein (CRP), we aimed to determine the leucocyte‐complement receptor 1 (L‐CR1) transcript levels and the relationship of this protein with the clinical disease activity of RA patients. Sixty‐six controls and 45 RA patients were enrolled. L‐CR1 transcript levels were correlated with the levels of circulating immune complexes (CIC), C3, C4 and C3d in controls and patients and with disease activity score 28 (DAS28) in patients only. CIC levels were determined by polyethylene glycol (PEG) precipitation, C3 and C4 levels by nephlometry and C3d levels by enzyme‐linked immunosorbent assay (ELISA). Eleven patients were recruited for follow‐up of L‐CR1 and DAS28 levels at weeks 0, 12 and 24. Appropriate statistical methods were used for the data analysis. L‐CR1 (P < 0·01) transcript levels were decreased in patients compared to controls. L‐CR1 levels correlated negatively with DAS28, CIC and C3d. DAS28 correlated positively with levels of CIC, C3 and C3d. Levels of CIC correlated positively with C3 and C3d. Levels of C3 correlated positively with C3d in patients and with C4 in both controls and patients. Levels of L‐CR1 increased with decline in DAS28 scores in follow‐up patients. Observations were statistically significant. Lower levels of L‐CR1 transcript in patients compared to controls, their correlations with the levels of CIC, C3d and DAS28 at different time‐points in RA patients suggest CR1 as a potential disease marker for RA.